Carbon-silicon negative electrode material as well as preparation method and application thereof

By introducing element-doped porous carbon matrix and nanosilicon particles into the carbon-silicon negative electrode material, solid electrolyte is formed, which solves the problems of low lithium ion transmission rate and electron conductivity, improves battery performance, and improves the gaseous carbon source through catalysts. Cracking efficiency reduces resource waste and environmental pollution.

CN119252894APending Publication Date: 2025-01-03SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 7 Cited by

Patent Information

Application Number
CN202411373184.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the preparation process, the existing carbon-silicon anode materials have low lithium ion transmission rate and poor silicon electron conductivity, resulting in poor battery performance, and waste of resources and serious environmental pollution of vapor deposition methods.

Method used

The combination of element-doped porous carbon matrix and nanosilicon particles is used to form a solid electrolyte through ball mill mixing and high-temperature carbonization treatment, which improves the lithium ion transmission rate and electron conductivity, and improves the cracking efficiency of the gaseous carbon source through catalysts.

Benefits of technology

The electronic conductivity of the battery, the first cycle efficiency and the 100 cycle capacity retention rate are improved, resource waste and environmental pollution are reduced, and efficient continuous production is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252894A_ABST
    Figure CN119252894A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-silicon negative electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: S1, carrying out mixed reaction on a lithium source compound, a lanthanum source compound and a titanium source compound to obtain a mixed reactant; mixing the mixed reactant with a carbon source compound, and dispersing and emulsifying to obtain element-doped microspheres; s2, carbonizing the element-doped microspheres in the step S1 to obtain carbides, and activating the carbides to obtain a porous carbon material; and S3, performing silicon deposition on the porous carbon material in the S2 to obtain silicon deposition porous carbon, and performing carbon deposition on the silicon deposition porous carbon to obtain the carbon-silicon negative electrode material. The carbon-silicon negative electrode material disclosed by the invention is high in lithium ion transmission rate, the problem of poor electronic conductivity of silicon is solved, and the electrical property of a battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon silicon negative electrode material, a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid popularization and development of portable electronic devices and electric vehicles, traditional graphite negative electrode materials can no longer meet the current market demand for batteries with high energy density and long cycle life. At present, the capacity of graphite negative electrode materials widely used in commercial lithium-ion batteries is around 360mAh / g, which is very close to its theoretical specific capacity (372mAh / g). Therefore, it is difficult to make further breakthroughs. It is urgent to find the next generation of lithium-ion battery negative electrode materials. Subsequently, people turned their attention to silicon materials. In lithium-ion batteries, silicon materials form Li at high temperatures. 22 Si5, corresponding to a specific capacity of 4200mAh / g, forms Li 15 Si4 has a specific capacity of 3579 mAh / g, and the delithiation potential of silicon is relatively low, so when silicon is used as a negative electrode, it can reduce the amount of materials used and increase the energy density of the battery. Based on this, silicon materials are an important development direction for negative electrode materials of power batteries.

[0003] Silicon-carbon negative electrode materials refer to materials that dope silicon materials with carbon materials of different structures to significantly improve the capacity and electrochemical performance of negative electrode materials. In order to solve the huge volume changes of carbon-silicon negative electrode materials during charging and discharging, as well as the problems of particle pulverization, uncontrollable growth of solid electrolyte interface phase (SEI), loss of electrical contact caused by poor electronic conductivity, the existing technology generally alleviates the above problems through porous structure design. In addition, in order to solve the mileage anxiety problem of electric vehicle users, it is imperative to further improve the energy density of batteries, and there are many ways to improve the energy density of batteries, such as optimizing the battery structure, increasing the energy density of active materials, and reducing the proportion of inactive materials.

[0004] Chinese patent CN116826017A discloses a silicon-carbon negative electrode material and a preparation method thereof, which specifically relates to the field of secondary battery technology. The silicon-carbon negative electrode material includes a silicon nanomaterial, a first carbon material, and a second carbon material; a plurality of the silicon nanomaterials are dispersed in the pores of the first carbon material and isolated by the pore walls of the first carbon material to form silicon-carbon primary particles; and a second carbon material matrix surrounding one or more of the silicon-carbon primary particles, wherein the silicon-carbon primary particles are dispersed and embedded in the second carbon material matrix. The design of the secondary structure of the silicon-carbon negative electrode material allows the silicon nanomaterial to be highly uniformly dispersed to a certain extent inside the negative electrode material. Under the buffering effect of the secondary carrier, the volume effect of the silicon material in the charge and discharge cycle is effectively alleviated, which greatly improves the cycle stability of the silicon-carbon negative electrode material and solves the problem of ultra-low electrode expansion rate while achieving high silicon loading in the negative electrode material.

[0005] However, the preparation method of the existing carbon-silicon negative electrode material similar to that in the above-mentioned patent document still has the following shortcomings: First, when preparing carbon-silicon negative electrode materials, the existing technology usually chooses to deposit a large amount of silicon in the pores of porous carbon, but the electrical conductivity of silicon material is relatively low, and the diffusion rate of lithium in silicon is also relatively low, which is not conducive to the transmission of lithium ions and electrons; Second, porous carbon-deposited silicon is generally carbon-coated by gas phase deposition of methane, acetylene and other gases to reduce the specific surface area, reduce defects, and improve the initial efficiency and cycle performance of the material, but the activity of carbon source gases such as methane and acetylene is low, and the cracking efficiency is low. A large amount of gas will be discharged with the carrier gas for combustion treatment, which ultimately leads to a large amount of resource waste and environmental pollution; Third, the temperature required for the cracking of carbon source gas is relatively high, which easily leads to the production of silicon carbide, thereby affecting the initial efficiency and capacity of the material. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a carbon-silicon negative electrode material and its preparation method and application in order to overcome the deficiencies of the prior art. The preparation method of the carbon-silicon negative electrode material provided by the present invention can not only improve the lithium ion transmission rate of the negative electrode material, but also effectively improve the problem of poor electronic conductivity of silicon itself, thereby improving the electronic conductivity, first cycle efficiency and 100-cycle cycle capacity retention rate of the battery; and the method is easy to operate, and can reduce resource waste and environmental pollution by effectively increasing the cracking efficiency of the gaseous carbon source. At the same time, it can realize continuous production and preparation, with short preparation time, high production efficiency, and high market application value.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The present invention provides a carbon-silicon negative electrode material, which comprises an element-doped porous carbon matrix and a coated carbon layer;

[0009] A solid electrolyte containing lithium, lanthanum and titanium is dispersed in the element-doped porous carbon matrix; the molar ratio of the lithium, lanthanum and titanium in the solid electrolyte is (0.120-0.510):(0.497-0.627):1; the mass percentage of the solid electrolyte in the carbon-silicon negative electrode material is 0.1wt.%-20wt.%;

[0010] Nano silicon particles are deposited on the outer surface and pore walls of the element-doped porous carbon matrix; the mass percentage of the nano silicon particles in the carbon silicon negative electrode material is 30wt.% to 60wt.%;

[0011] The mass percentage of the coated carbon layer to the carbon-silicon negative electrode material is 0.5wt.% to 10wt.%.

[0012] In the present invention, the molar ratio of the lithium element, the lanthanum element and the titanium element in the solid electrolyte is preferably (0.3-0.5):(0.5-0.6):1.

[0013] In the present invention, the mass percentage of the solid electrolyte to the carbon-silicon negative electrode material is preferably 5wt.% to 10wt.%.

[0014] In the present invention, the mass percentage of the nano-silicon particles in the carbon-silicon negative electrode material is preferably 45wt.% to 55wt.%, for example, 49.5wt.%, 49.8wt.% or 49.9wt.%.

[0015] In the present invention, the mass percentage of the coated carbon layer to the carbon-silicon negative electrode material is preferably 2 wt.% to 6 wt.%, for example: 3.0 wt.%, 4.0 wt.% or 4.1 wt.%.

[0016] In the present invention, the D50 particle size of the carbon silicon negative electrode material is preferably 1 to 50 μm, more preferably 5 to 15 μm, for example 8.0 μm or 8.1 μm.

[0017] In the present invention, the sphericity of the carbon silicon negative electrode material is preferably 0.8 to 0.99, more preferably 0.9 to 0.99, for example: 0.973, 0.976, 0.969.

[0018] In the present invention, the specific surface area of ​​the carbon silicon negative electrode material is preferably 0.1 to 20 m 2 / g, more preferably 1 to 5 m 2 / g, for example: 2.7m 2 / g, 2.8m 2 / g or 3.0m 2 / g.

[0019] In the present invention, the average pore diameter of the element-doped porous carbon matrix is ​​preferably 0.1-100 nm, more preferably 1-10 nm, for example, 1.71 nm, 1.74 nm or 1.78 nm.

[0020] In the present invention, the pore volume of the element-doped porous carbon matrix is ​​preferably 0.1 to 2 cm 3 / g, more preferably 0.1 to 1 cm 3 / g, for example: 0.79cm 3 / g, 0.84cm 3 / g or 0.86cm 3 / g.

[0021] The present invention provides a method for preparing a carbon-silicon negative electrode material, which comprises the following steps:

[0022] S1. Preparation of element-doped microspheres:

[0023] The lithium source compound, the lanthanum source compound and the titanium source compound are mixed and reacted to obtain a mixed reactant; the mixed reactant is mixed with a carbon source compound for dispersion and emulsification to obtain element-doped microspheres;

[0024] S2. Preparation of porous carbon:

[0025] First, the microspheres doped with the element described in S1 are carbonized to obtain carbides, and then activated to obtain porous carbon materials;

[0026] S3. Preparation of carbon silicon negative electrode materials:

[0027] The porous carbon material in S2 is subjected to silicon deposition to obtain silicon-deposited porous carbon, and then the silicon-deposited porous carbon is subjected to carbon deposition to obtain a carbon-silicon negative electrode material.

[0028] In the present invention, in step S1, the lithium source compound preferably includes one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium acetate, lithium sulfate and lithium perchlorate, for example, lithium hydroxide or lithium carbonate.

[0029] In the present invention, in step S1, the lanthanum source compound preferably includes one or more of lanthanum oxide, lanthanum hydroxide, lanthanum chloride, lanthanum acetate and lanthanum nitrate, for example, lanthanum oxide or lanthanum hydroxide.

[0030] In the present invention, in step S1, the titanium source compound preferably includes one or more of titanium oxide, tetraethyl titanate, tetrabutyl titanate, titanium acetylacetonate, titanium tetrachloride, isopropyl titanate, titanium oxysulfate and titanium trichloride, for example, titanium oxide.

[0031] In the present invention, in step S1, the molar ratio of the lithium source compound, the lanthanum source compound and the titanium source compound is preferably (0.12-0.51):(0.16-0.55):1, more preferably (0.3-0.5):(0.2-0.4):1, for example: 0.33:0.29:1 or 0.5:0.25:1.

[0032] In the present invention, in step S1, the carbon source compound preferably includes one or more of phenolic resin, epoxy resin, polyvinyl alcohol resin, polyimide resin, polyacrylonitrile, furfural, asphalt, sucrose and cellulose, for example, phenolic resin.

[0033] In the present invention, in step S1, the mass percentage of the mixed reactants to the carbon source compound is preferably 1wt.% to 99wt.%, more preferably 1wt.% to 10wt.%, for example 3wt.%, 5wt.% or 8wt.%.

[0034] In the present invention, in step S1, the mixing reaction is preferably ball milling mixing.

[0035] The ball milling mixing is preferably performed by dry milling.

[0036] The ball milling speed is preferably 100 to 2000 rpm, more preferably 200 to 1200 rpm. rpm, for example For example: 300rpm, 500rpm or 1000rpm.

[0037] The mass ratio of the ball materials mixed by ball milling is preferably (1-40):1, more preferably (15-25):1, for example: 20:1.

[0038] The ball milling mixing time is preferably 0.5 to 6 hours, more preferably 2 to 6 hours, for example 3 hours, 4 hours or 5 hours.

[0039] In the present invention, the ball milling mixing can realize the crushing of powder into nano-sized particles, and utilize the energy generated by the high-speed rotation to cause chemical reaction between the particles of the solid material.

[0040] In the present invention, in step S1, the dispersion and emulsification is preferably carried out in a homogenizer.

[0041] In the present invention, in step S1, the pressure of the dispersion and emulsification is preferably 3 to 100 MPa, more preferably 10 to 50 MPa, for example 20 MPa, 30 MPa or 40 MPa.

[0042] In the present invention, in step S1, the temperature of the dispersion and emulsification is preferably 10-60°C, more preferably 10-20°C.

[0043] In the present invention, in step S1, the dispersion and emulsification time is preferably 10 to 120 minutes, more preferably 10 to 40 minutes, for example, 15 minutes or 30 minutes.

[0044] In the present invention, in step S1, the dispersion and emulsification preferably further include centrifugation and drying operations.

[0045] The centrifugation time is preferably 10 to 60 min, more preferably 20 to 50 min, for example 30 min or 45 min.

[0046] The drying temperature is preferably 50-300°C, more preferably 100-250°C, for example 150°C, 180°C or 200°C.

[0047] The drying time is preferably 0.5 to 12 hours, more preferably 2 to 8 hours, for example 4 hours, 5 hours or 6 hours.

[0048] In the present invention, in step S2, the carbonization operation preferably includes crushing and classification operations before the carbonization operation.

[0049] Wherein, the classification is preferably carried out in a cyclone separator.

[0050] In the present invention, in step S2, the carbonization is preferably performed in a tube furnace.

[0051] In the present invention, in step S2, the carbonization is preferably performed under a nitrogen atmosphere.

[0052] In the present invention, in step S2, the heating rate of the carbonization is preferably 0.5-20°C / min, more preferably 1-12°C / min, for example 3°C / min, 5°C / min or 10°C / min.

[0053] In the present invention, in step S2, the carbonization temperature is preferably 300-800°C, more preferably 500-800°C, for example 600°C or 700°C.

[0054] In the present invention, in step S2, the carbonization time is preferably 0.5 to 5 hours, more preferably 1 to 4 hours, for example 1 hour, 2 hours or 4 hours; the carbonization time refers to the time of keeping warm at the carbonization temperature, excluding the heating time.

[0055] In the present invention, in step S2, the activation operation is preferably to introduce an activation medium to perform pore-forming treatment.

[0056] In the present invention, in step S2, the activation is preferably performed under a nitrogen atmosphere.

[0057] In the present invention, in step S2, the activation heating rate is preferably 0.5-20°C / min, more preferably 1-12°C / min, for example 3°C / min, 5°C / min or 10°C / min.

[0058] In the present invention, in step S2, the activation temperature is preferably 600-1100°C, more preferably 700-1000°C, for example 800°C, 900°C or 950°C.

[0059] In the present invention, in step S2, the activation time is preferably 1 to 10 hours, more preferably 2 to 7 hours, for example 3 hours, 5 hours or 6 hours; the activation time refers to the time for introducing the activation medium at the activation temperature, excluding the heating time.

[0060] In the present invention, in step S2, the activation medium is preferably water vapor or carbon dioxide.

[0061] Wherein, when the activation medium is water vapor, the usage amount of the water vapor is preferably 0.01-1 mL / g carbide / min, more preferably 0.01-0.05 mL / g carbide / min, for example: 0.01 mL / g carbide / min or 0.03 mL / g carbide / min; mL / g carbide / min refers to the volume of water vapor that needs to be introduced per gram of carbide per minute during the activation process.

[0062] Among them, when the activation medium is carbon dioxide, the molar ratio of the carbide to the carbon dioxide is preferably 1: (0.5-1.5), more preferably 1: (0.8-1.2), for example: 1:1; the flow rate of the carbon dioxide is preferably 1-20 L / min, more preferably 1-10 L / min, for example: 3 L / min.

[0063] In the present invention, in step S3, the silicon deposition is preferably performed in a fluidized bed.

[0064] Wherein, the deposition chamber pressure of the fluidized bed is preferably ≤200 Pa.

[0065] In the present invention, in step S3, the silicon deposition is preferably performed under a nitrogen atmosphere.

[0066] In the present invention, in step S3, the silicon deposition operation is preferably performed by introducing a gaseous silicon source into the porous carbon material.

[0067] The flow rate of the gaseous silicon source is preferably 0.5-20 L / min, more preferably 1-10 L / min, for example 5 L / min.

[0068] The gaseous silicon source preferably includes one or more of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorosilane, trichlorosilane, silicon tetrachloride and silicon tetrafluoride, for example, monosilane.

[0069] In the present invention, in step S3, the temperature of silicon deposition is preferably 300-1000°C, more preferably 500-800°C, for example 650°C.

[0070] In the present invention, in step S3, the silicon deposition time is preferably 0.1 to 6 hours, more preferably 1 to 3 hours, for example, 1 hour, 1.5 hours or 2 hours.

[0071] In the present invention, in step S3, the carbon deposition is preferably performed in a fluidized bed.

[0072] Wherein, the deposition chamber pressure of the fluidized bed is preferably ≤200 Pa.

[0073] In the present invention, in step S3, the carbon deposition is preferably performed under a nitrogen atmosphere.

[0074] In the present invention, in step S3, the carbon deposition operation is preferably performed by introducing a gaseous carbon source into the silicon-deposited porous carbon.

[0075] The flow rate of the gaseous carbon source is preferably 0.1 to 3 L / min, more preferably 0.1 to 1 L / min, for example 0.5 L / min.

[0076] The gaseous carbon source preferably includes one or more of methane, ethane, propane, acetylene, propyne, butyne and ethylene, for example, acetylene.

[0077] In the present invention, in step S3, the temperature of the carbon deposition is preferably 300-1100°C, more preferably 300-700°C, for example 350°C, 450°C or 550°C.

[0078] In the present invention, in step S3, the carbon deposition time is preferably 0.5 to 6 hours, more preferably 0.5 to 2 hours, for example 0.5 hours or 1 hour.

[0079] The present invention also provides a carbon silicon negative electrode material, which is prepared by the method for preparing the carbon silicon negative electrode material as described above.

[0080] The present invention also provides an application of the carbon silicon negative electrode material as described above in the field of batteries.

[0081] In the present invention, the lithium source compound, lanthanum source compound and titanium source compound mixed by ball milling are dispersed in the carbon source compound, and are evenly dispersed inside and on the surface of the carbon source compound. After subsequent high-temperature treatment, the lithium source compound, lanthanum source compound and titanium source compound form a solid electrolyte, lithium lanthanum titanate, whose chemical formula is Li 3x La 2 / 3–x TiO3, 0.04<x<0.17, chemical formula for example: Li 0.33 La 0.57 TiO3 can not only improve the lithium ion transmission rate of the negative electrode material, but also effectively improve the poor electronic conductivity of silicon itself, thereby improving the electronic conductivity of the silicon-carbon composite material; in addition, the first cycle efficiency of the silicon-carbon material can be improved by embedding the lithium source. In addition, the above-mentioned solid electrolyte lithium lanthanum titanate is a catalyst that catalyzes the cracking of gaseous carbon sources such as acetylene, so it can not only improve the cracking speed and utilization rate of the gaseous carbon source; but also reduce the cracking temperature and reduce the formation of silicon carbide.

[0082] In the present invention, the homogenization treatment of the lithium source compound, the lanthanum source compound, the titanium source compound and the carbon source compound can not only control the particle size by the homogenization pressure, but also the prepared silicon-carbon negative electrode material has a smooth morphology, a regular shape, and a high sphericity, which can improve the high-temperature cycle performance and high-temperature storage performance of the silicon-based negative electrode material. In addition, the silicon-carbon negative electrode material prepared by the present invention is also conducive to improving the compressive strength and compaction density of the negative electrode material, and avoiding the battery pole piece from being broken and pulverized during the rolling process.

[0083] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0084] The reagents and raw materials used in the present invention are commercially available.

[0085] The positive and progressive effects of the present invention are:

[0086] (1) The preparation method of the carbon-silicon negative electrode material of the present invention can not only improve the lithium ion transmission rate of the negative electrode material, but also effectively improve the problem of poor electronic conductivity of silicon itself, thereby improving the electronic conductivity, first cycle efficiency and 100-cycle cycle capacity retention rate of the battery.

[0087] (2) The preparation method of the carbon-silicon negative electrode material of the present invention is easy to operate and can reduce resource waste and environmental pollution by effectively increasing the cracking efficiency of the gaseous carbon source. At the same time, it can realize continuous production and preparation with short preparation time and high production efficiency, and has high market application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] Figure 1 This is a SEM image of the carbon-silicon negative electrode material prepared in Example 1 of the present invention.

[0089] Figure 2 This is a SEM image of the carbon-silicon negative electrode material prepared in Example 2 of the present invention.

[0090] Figure 3 This is a SEM image of the carbon-silicon negative electrode material prepared in Example 3 of the present invention.

[0091] Figure 4 This is a SEM image of the carbon-silicon negative electrode material prepared in Comparative Example 1 of the present invention.

[0092] Figure 5 This is a SEM image of the carbon-silicon negative electrode material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0093] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0094] Example 1

[0095] S1. Preparation of element-doped microspheres:

[0096] The raw materials LiOH, La2O3 and TiO2 were weighed in a molar ratio of 0.33:0.25:1, added to a ball mill and mixed evenly, the ball mill speed was 500 rpm, the ball-to-material mass ratio was 20:1, and the ball milling time was 4 h. The mixed reactants after ball milling (5 wt.% of the mass of the phenolic resin) were added to the phenolic resin, and after continuing to stir and disperse evenly, they were dispersed and emulsified in a homogenizer for 15 min. The pressure of the homogenizer was 20 MPa, and the temperature of the homogenizer was maintained below 20°C. After centrifugation for 30 min, the mixture was dried at 150°C for 5 h to obtain element-doped microspheres.

[0097] S2. Preparation of porous carbon:

[0098] The above-mentioned element-doped microspheres were placed in a tubular furnace, and in a nitrogen protective atmosphere, the temperature was raised to 600°C at a rate of 5°C / min, maintained at 600°C for 2 hours, and then cooled to room temperature to obtain carbides; then in a nitrogen atmosphere, the temperature was raised to 800°C at a rate of 3°C / min, and then water vapor was introduced in an amount of 0.01 mL / g carbide / min for 5 hours, and the temperature was cooled to room temperature to obtain a porous carbon material.

[0099] S3. Preparation of carbon silicon negative electrode materials:

[0100] The porous carbon material is placed in a fluidized bed, and nitrogen is introduced to replace the air under vacuum. The reaction temperature is controlled at 650°C, the pressure of the deposition chamber of the fluidized bed is ≤200 Pa, and monosilane is introduced at a flow rate of 5 L / min to perform silicon deposition for 1 hour to obtain silicon-deposited porous carbon;

[0101] The temperature of the fluidized bed was controlled at 450° C., acetylene was introduced at a flow rate of 0.5 L / min, and carbon deposition was performed for 0.5 h to obtain a silicon-carbon negative electrode material.

[0102] Example 2

[0103] S1. Preparation of element-doped microspheres:

[0104] The raw materials Li2CO3, La2O3 and TiO2 were weighed at a molar ratio of 0.4:0.25:1, added to a ball mill and mixed evenly. The ball mill speed was 1000 rpm, the ball-to-material mass ratio was 20:1, and the ball milling time was 3 h. The mixed reactants after ball milling (3 wt.% of the mass of the phenolic resin) were added to the phenolic resin. After continuing to stir and disperse evenly, they were dispersed and emulsified in a homogenizer for 30 min. The pressure of the homogenizer was 30 MPa, and the temperature of the homogenizer was maintained below 20°C. After centrifugation for 60 min, the mixture was dried at 180°C for 6 h to obtain element-doped microspheres.

[0105] S2. Preparation of porous carbon:

[0106] The above-mentioned element-doped microspheres were placed in a tubular furnace, and in a nitrogen protective atmosphere, the temperature was raised to 600°C at a rate of 10°C / min, maintained at 600°C for 4 hours, and then cooled to room temperature to obtain carbides; then in a nitrogen atmosphere, the temperature was raised to 950°C at a rate of 5°C / min, and then water vapor was introduced at a rate of 0.03 mL / g carbide / min for 3 hours, and the temperature was cooled to room temperature to obtain a porous carbon material.

[0107] S3. Preparation of carbon silicon negative electrode materials:

[0108] The porous carbon material is placed in a fluidized bed, and nitrogen is introduced to replace the air under vacuum. The reaction temperature is controlled at 650°C, the pressure of the deposition chamber of the fluidized bed is ≤200 Pa, and monosilane is introduced at a flow rate of 5 L / min to perform silicon deposition for 2 hours to obtain silicon-deposited porous carbon;

[0109] The temperature of the fluidized bed was controlled at 350°C, acetylene was introduced at a flow rate of 0.5 L / min, and carbon deposition was performed for 1 hour to obtain a silicon-carbon negative electrode material.

[0110] Example 3

[0111] S1. Preparation of element-doped microspheres:

[0112] The raw materials LiOH, La(OH)3 and TiO2 were weighed at a molar ratio of 0.5:0.5:1, added to a ball mill and mixed evenly, the ball mill speed was 300 rpm, the ball-to-material mass ratio was 20:1, and the ball milling time was 5 h. The mixed reactants after ball milling (8 wt.% of the mass of the phenolic resin) were added to the phenolic resin, and after continuing to stir and disperse evenly, they were dispersed and emulsified in a homogenizer for 30 min. The pressure of the homogenizer was 40 MPa, and the temperature of the homogenizer was maintained below 20°C. After centrifugation for 45 min, the mixture was dried at 200°C for 4 h to obtain element-doped microspheres.

[0113] S2. Preparation of porous carbon:

[0114] The above-mentioned element-doped microspheres were placed in a tubular furnace, and in a nitrogen protective atmosphere, the temperature was raised to 700°C at a rate of 3°C / min, maintained at 700°C for 1 hour, and then cooled to room temperature to obtain carbides; then in a nitrogen atmosphere, the temperature was raised to 900°C at a rate of 10°C / min, and then carbon dioxide was introduced with a molar ratio of carbide to carbon dioxide of 1:1, a flow rate of carbon dioxide of 3L / min, and a duration of 6 hours. The temperature was cooled to room temperature to obtain a porous carbon material.

[0115] S3. Preparation of carbon silicon negative electrode materials:

[0116] The porous carbon material was placed in a fluidized bed, and nitrogen was introduced to replace the air under vacuum. The reaction temperature was controlled at 650°C, the pressure of the deposition chamber of the fluidized bed was ≤200 Pa, and monosilane was introduced at a flow rate of 5 L / min to perform silicon deposition for 1.5 hours to obtain silicon-deposited porous carbon;

[0117] The temperature of the fluidized bed was controlled at 550° C., acetylene was introduced at a flow rate of 0.5 L / min, and carbon deposition was performed for 0.5 h to obtain a silicon-carbon negative electrode material.

[0118] Comparative Example 1

[0119] S1. Microsphere preparation:

[0120] The phenolic resin of the same mass as that in Example 1 was stirred and dispersed uniformly, and then dispersed and emulsified in a homogenizer for 15 minutes. The pressure of the homogenizer was 20 MPa, and the temperature of the homogenizer was maintained below 20°C. After centrifugation for 30 minutes, the element-doped microspheres were dried at 150°C for 5 hours.

[0121] S2. Preparation of porous carbon:

[0122] The above-mentioned element-doped microspheres were placed in a tubular furnace, and in a nitrogen protective atmosphere, the temperature was raised to 600°C at a rate of 5°C / min, maintained at 600°C for 2 hours, and then cooled to room temperature to obtain carbides; then in a nitrogen atmosphere, the temperature was raised to 800°C at a rate of 3°C / min, and then water vapor was introduced in an amount of 0.01 mL / g carbide / min for 5 hours, and the temperature was cooled to room temperature to obtain a porous carbon material.

[0123] S3. Preparation of carbon silicon negative electrode materials:

[0124] The porous carbon material is placed in a fluidized bed, and nitrogen is introduced to replace the air under vacuum. The reaction temperature is controlled at 650°C, the pressure of the deposition chamber of the fluidized bed is ≤200 Pa, and monosilane is introduced at a flow rate of 5 L / min to perform silicon deposition for 1 hour to obtain silicon-deposited porous carbon;

[0125] The temperature of the fluidized bed was controlled at 450° C., acetylene was introduced at a flow rate of 0.5 L / min, and carbon deposition was performed for 0.5 h to obtain a silicon-carbon negative electrode material.

[0126] Comparative Example 2

[0127] S1. Microsphere preparation:

[0128] The phenolic resin of the same mass as that in Example 1 was stirred and dispersed uniformly, and then dispersed and emulsified in a homogenizer for 15 minutes. The pressure of the homogenizer was 20 MPa, and the temperature of the homogenizer was maintained below 20°C. After centrifugation for 30 minutes, the element-doped microspheres were dried at 150°C for 5 hours.

[0129] S2. Preparation of porous carbon:

[0130] The above-mentioned element-doped microspheres were placed in a tubular furnace, and in a nitrogen protective atmosphere, the temperature was raised to 600°C at a rate of 5°C / min, maintained at 600°C for 2 hours, and then cooled to room temperature to obtain carbides; then in a nitrogen atmosphere, the temperature was raised to 800°C at a rate of 3°C / min, and then water vapor was introduced in an amount of 0.01 mL / g carbide / min for 5 hours, and the temperature was cooled to room temperature to obtain a porous carbon material.

[0131] S3. Preparation of carbon silicon negative electrode materials:

[0132] The porous carbon material is placed in a fluidized bed, and nitrogen is introduced to replace the air under vacuum. The reaction temperature is controlled at 650°C, the pressure of the deposition chamber of the fluidized bed is ≤200 Pa, and monosilane is introduced at a flow rate of 5 L / min to perform silicon deposition for 1 hour to obtain silicon-deposited porous carbon;

[0133] The temperature of the fluidized bed was controlled at 450°C, acetylene was introduced at a flow rate of 0.5 L / min, and carbon deposition was performed for 6 hours to obtain a silicon-carbon negative electrode material.

[0134] The silicon-carbon negative electrode materials provided in Examples 1-3 and Comparative Examples 1-2 are respectively assembled into batteries, and the steps are as follows:

[0135] (1) Preparation of pole pieces: Silicon-carbon negative electrode material, conductive agent (Super-P), and polyacrylic acid (PAA) binder were mixed in a mass ratio of 80:10:10 to prepare a slurry, stirred and mixed, and then coated on a copper foil current collector. After drying at room temperature, the slurry was placed in a vacuum oven and further dried at 60°C for 12 h to obtain a pole piece.

[0136] (2) Battery assembly: The electrode obtained above was cut into a circular electrode with a diameter of 10 mm and an active material loading of 1.3 mg / cm 2Metal lithium sheet was used as the counter electrode, 1 mol / L LiPF6 (the solvent was a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, with 5% volume of fluoroethylene carbonate added) as the electrolyte, and a polypropylene microporous membrane was assembled into a 2032 type button cell in an argon atmosphere glove box, with 50 μL of electrolyte added to each cell.

[0137] Effect Example 1

[0138] Testing of silicon-carbon anode materials

[0139] (1) Surface morphology test

[0140] ①Test method

[0141] The present invention uses a scanning electron microscope (SEM, German ZEISS, sigma 300) to test the surface morphology of the silicon-carbon negative electrode material.

[0142] ②Test results

[0143] Figure 1-3 They are the SEM images of Examples 1-3, Figure 4-5 They are SEM images of Comparative Examples 1-2 respectively. Figure 1-3 It can be seen that the silicon-carbon negative electrode material prepared in the present invention has high sphericity of particles, uniform particle size distribution, and no adhesion between particles.

[0144] (2) Material property test

[0145] ①Test method

[0146] The present invention tests the specific surface area of ​​the silicon-carbon negative electrode material according to GB / T19587-2017; the present invention tests the D50 particle size of the silicon-carbon negative electrode material according to GB / T24533-2019; the present invention tests the mass percentage of the coated carbon layer of the silicon-carbon negative electrode material according to YS / T 1509.2-2021; the present invention tests the mass percentage of nano-silicon particles of the silicon-carbon negative electrode material according to YS / T 1509.1-2021; the present invention uses an image particle size analyzer (Japan Seishin PITA-04) to test the sphericity of the silicon-carbon negative electrode material.

[0147] ②Test results

[0148] The relevant property tests of the silicon-carbon negative electrode materials of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.

[0149] Table 1

[0150]

[0151] Effect Example 2

[0152] Powder resistivity test of battery

[0153] ①Test method

[0154] The present invention adopts a semiconductor powder resistivity test method (four-probe method) to test the powder resistivity of the battery under a pressure of 20 MPa.

[0155] ②Test results

[0156] It can be seen from Table 2 that the powder resistivity of Examples 1-3 is much smaller than that of Comparative Examples 1-2, indicating that the battery made of the carbon-silicon negative electrode material prepared by the present invention has excellent electronic conductivity.

[0157] Table 2

[0158]

[0159] Effect Example 3

[0160] Battery electrical performance test

[0161] ①Test method

[0162] The invention adopts a blue electric tester CT3002A to test the electrical performance of the prepared button battery, and the charge and discharge cut-off voltages are 1.5V and 0.005V respectively. Then, activation is carried out under a 0.05C rate condition and a charge and discharge cycle test is carried out under a 0.5C rate condition to obtain the first-cycle charging specific capacity, the first-cycle cycle coulomb efficiency and the 100-cycle cycle capacity retention rate of the battery.

[0163] ②Test results

[0164] It can be seen from Table 2 that the charge specific capacity, first cycle coulombic efficiency and 100-cycle capacity retention rate of Examples 1-3 are significantly higher than those of Comparative Examples 1-2, that is, the batteries prepared using the carbon-silicon negative electrode material prepared by the present invention have significantly improved first cycle charge specific capacity, first cycle efficiency and 100-cycle capacity retention rate.

Claims

1. A carbon silicon negative electrode material, characterized in that: The carbon silicon negative electrode material comprises an element-doped porous carbon matrix and a coated carbon layer; A solid electrolyte containing lithium, lanthanum and titanium is dispersed in the element-doped porous carbon matrix; the molar ratio of the lithium, lanthanum and titanium in the solid electrolyte is (0.120-0.510):(0.497-0.627):1; the mass percentage of the solid electrolyte in the carbon-silicon negative electrode material is 0.1wt.%-20wt.%; Nano silicon particles are deposited on the outer surface and pore walls of the element-doped porous carbon matrix; the mass percentage of the nano silicon particles in the carbon silicon negative electrode material is 30wt.% to 60wt.%; The mass percentage of the coated carbon layer to the carbon-silicon negative electrode material is 0.5wt.% to 10wt.%.

2. The carbon-silicon negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The molar ratio of the lithium element, the lanthanum element and the titanium element in the solid electrolyte is (0.3-0.5): (0.5-0.6): 1; (2) The mass percentage of the solid electrolyte to the carbon-silicon negative electrode material is 5wt.% to 10wt.%; (3) The mass percentage of the nano-silicon particles to the carbon-silicon negative electrode material is 45 wt.% to 55 wt.%, for example: 49.5 wt.%, 49.8 wt.% or 49.9 wt.%; (4) The mass percentage of the coated carbon layer to the carbon-silicon negative electrode material is 2 wt.% to 6 wt.%, for example: 3.0 wt.%, 4.0 wt.% or 4.1 wt.%; (5) The D50 particle size of the carbon silicon negative electrode material is 1 to 50 μm, preferably 5 to 15 μm, for example 8.0 μm or 8.1 μm; (6) The sphericity of the carbon silicon negative electrode material is 0.8 to 0.99, preferably 0.9 to 0.99, for example: 0.973, 0.976, 0.969; (7) The specific surface area of ​​the carbon silicon negative electrode material is 0.1 to 20 m 2 / g, preferably 1 to 5 m 2 / g, for example: 2.7m 2 / g, 2.8m 2 / g or 3.0m 2 / g; (8) The average pore size of the element-doped porous carbon matrix is ​​0.1 to 100 nm, preferably 1 to 10 nm, for example, 1.71 nm, 1.74 nm or 1.78 nm; and (9) The pore volume of the element-doped porous carbon matrix is ​​0.1 to 2 cm 3 / g, preferably 0.1-1cm 3 / g, for example: 0.79cm 3 / g, 0.84cm 3 / g or 0.86cm 3 / g.

3. A method for preparing a carbon-silicon negative electrode material, characterized in that: It includes the following steps: S1. Preparation of element-doped microspheres: The lithium source compound, the lanthanum source compound and the titanium source compound are mixed and reacted to obtain a mixed reactant; the mixed reactant is mixed with a carbon source compound for dispersion and emulsification to obtain element-doped microspheres; S2. Preparation of porous carbon: First, the microspheres doped with the element described in S1 are carbonized to obtain carbides, and then activated to obtain porous carbon materials; S3. Preparation of carbon silicon negative electrode materials: The porous carbon material in S2 is subjected to silicon deposition to obtain silicon-deposited porous carbon, and then the silicon-deposited porous carbon is subjected to carbon deposition to obtain a carbon-silicon negative electrode material.

4. The method for preparing the carbon-silicon negative electrode material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In step S1, the lithium source compound includes one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium acetate, lithium sulfate and lithium perchlorate, for example, lithium hydroxide or lithium carbonate; (2) In step S1, the lanthanum source compound includes one or more of lanthanum oxide, lanthanum hydroxide, lanthanum chloride, lanthanum acetate and lanthanum nitrate, for example, lanthanum oxide or lanthanum hydroxide; (3) In step S1, the titanium source compound includes one or more of titanium oxide, tetraethyl titanate, tetrabutyl titanate, titanium acetylacetonate, titanium tetrachloride, isopropyl titanate, titanium oxysulfate and titanium trichloride, for example, titanium oxide; (4) In step S1, the molar ratio of the lithium source compound, the lanthanum source compound and the titanium source compound is (0.12-0.51):(0.16-0.55):1, preferably (0.3-0.5):(0.2-0.4):1, for example: 0.33:0.29:1 or 0.5:0.25:1; (5) In step S1, the carbon source compound includes one or more of phenolic resin, epoxy resin, polyvinyl alcohol resin, polyimide resin, polyacrylonitrile, furfural, asphalt, sucrose and cellulose, for example, phenolic resin; and (6) In step S1, the mass percentage of the mixed reactants to the carbon source compound is 1 wt.% to 99 wt.%, preferably 1 wt.% to 10 wt.%, for example 3 wt.%, 5 wt.% or 8 wt.%.

5. The method for preparing the carbon-silicon negative electrode material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In step S1, the mixing reaction is ball milling mixing; Wherein, the ball milling mixing is preferably carried out by dry milling; The ball milling speed is preferably 100 to 2000 rpm, more preferably 200 to 1200 rpm, for example 300 rpm, 500 rpm or 1000 rpm. The mass ratio of the ball materials mixed by ball milling is preferably (1-40):1, more preferably (15-25):1, for example: 20:1; The ball milling mixing time is preferably 0.5 to 6 hours, more preferably 2 to 6 hours, for example 3 hours, 4 hours or 5 hours; (2) In step S1, the dispersion and emulsification is carried out in a homogenizer; (3) In step S1, the dispersion and emulsification pressure is 3 to 100 MPa, preferably 10 to 50 MPa, for example, 20 MPa, 30 MPa or 40 MPa; (4) In step S1, the dispersion and emulsification temperature is 10 to 60° C., preferably 10 to 20° C.; (5) In step S1, the dispersion and emulsification time is 10 to 120 minutes, preferably 10 to 40 minutes, for example, 15 minutes or 30 minutes; and (6) In step S1, the dispersion and emulsification further include centrifugation and drying operations; Wherein, the centrifugation time is preferably 10 to 60 min, more preferably 20 to 50 min, for example: 30 min or 45 min; The drying temperature is preferably 50-300°C, more preferably 100-250°C, for example 150°C, 180°C or 200°C; The drying time is preferably 0.5 to 12 hours, more preferably 2 to 8 hours, for example 4 hours, 5 hours or 6 hours.

6. The method for preparing the carbon-silicon negative electrode material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In step S2, the carbonization operation includes crushing and classification operations; Wherein, the classification is preferably carried out in a cyclone separator; (2) In step S2, the carbonization is carried out in a tubular furnace; (3) In step S2, the carbonization is carried out under a nitrogen atmosphere; (4) In step S2, the carbonization heating rate is 0.5 to 20°C / min, preferably 1 to 12°C / min, for example, 3°C / min, 5°C / min or 10°C / min; (5) In step S2, the carbonization temperature is 300-800°C, preferably 500-800°C, for example 600°C or 700°C; and (6) In step S2, the carbonization time is 0.5 to 5 hours, preferably 1 to 4 hours, for example, 1 hour, 2 hours or 4 hours; the carbonization time refers to the time of keeping warm at the carbonization temperature, excluding the heating time.

7. The method for preparing the carbon-silicon negative electrode material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In step S2, the activation operation is to introduce an activation medium to perform pore-forming treatment; (2) In step S2, the activation is performed under a nitrogen atmosphere; (3) In step S2, the activation heating rate is 0.5 to 20°C / min, preferably 1 to 12°C / min, for example 3°C / min, 5°C / min or 10°C / min; (4) In step S2, the activation temperature is 600-1100°C, preferably 700-1000°C, for example 800°C, 900°C or 950°C; (5) In step S2, the activation time is 1 to 10 hours, preferably 2 to 7 hours, for example, 3 hours, 5 hours or 6 hours; the activation time refers to the time for introducing the activation medium at the activation temperature, excluding the heating time; and (6) In step S2, the activation medium is water vapor or carbon dioxide; Wherein, when the activation medium is water vapor, the usage amount of the water vapor is preferably 0.01-1 mL / g carbide / min, more preferably 0.01-0.05 mL / g carbide / min, for example: 0.01 mL / g carbide / min or 0.03 mL / g carbide / min; mL / g carbide / min refers to the volume of water vapor that needs to be introduced per gram of carbide per minute during the activation process; Among them, when the activation medium is carbon dioxide, the molar ratio of the carbide to the carbon dioxide is preferably 1: (0.5-1.5), more preferably 1: (0.8-1.2), for example: 1:1; the flow rate of the carbon dioxide is preferably 1-20 L / min, more preferably 1-10 L / min, for example: 3 L / min.

8. The method for preparing the carbon-silicon negative electrode material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In step S3, the silicon deposition is carried out in a fluidized bed; Wherein, the deposition chamber pressure of the fluidized bed is preferably ≤200 Pa; (2) In step S3, the silicon deposition is performed under a nitrogen atmosphere; (3) In step S3, the silicon deposition operation is to introduce a gaseous silicon source into the porous carbon material; Wherein, the flow rate of the gaseous silicon source is preferably 0.5-20 L / min, more preferably 1-10 L / min, for example: 5 L / min; Wherein, the gaseous silicon source preferably includes one or more of monosilane, disilane, trisilane, dimethylsilane, hexamethyldisilane, dichlorodihydrogensilane, trichlorosilane, silicon tetrachloride and silicon tetrafluoride, for example: monosilane; (4) In step S3, the temperature of silicon deposition is 300-1000° C., preferably 500-800° C., for example 650° C.; (5) In step S3, the silicon deposition time is 0.1 to 6 hours, preferably 1 to 3 hours, for example, 1 hour, 1.5 hours or 2 hours; (6) In step S3, the carbon deposition is carried out in a fluidized bed; Wherein, the deposition chamber pressure of the fluidized bed is preferably ≤200 Pa; (7) In step S3, the carbon deposition is performed under a nitrogen atmosphere; (8) In step S3, the carbon deposition operation is to introduce a gaseous carbon source into the silicon-deposited porous carbon; Wherein, the flow rate of the gaseous carbon source is preferably 0.1 to 3 L / min, more preferably 0.1 to 1 L / min, for example: 0.5 L / min; Wherein, the gaseous carbon source preferably includes one or more of methane, ethane, propane, acetylene, propyne, butyne and ethylene, for example: acetylene; (9) In step S3, the temperature of the carbon deposition is 300-1100°C, preferably 300-700°C, for example, 350°C, 450°C or 550°C; and (10) In step S3, the carbon deposition time is 0.5 to 6 hours, preferably 0.5 to 2 hours, for example 0.5 hours or 1 hour.

9. A carbon silicon negative electrode material, characterized in that: It is prepared by the method for preparing the carbon-silicon negative electrode material as described in any one of claims 3 to 8.

10. Use of the carbon silicon negative electrode material as claimed in claim 1 or 9 in the field of batteries.

Citation Information

Cited By

  • Silicon-carbon negative electrode material with multi-layer core-shell structure as well as preparation method and application of silicon-carbon negative electrode material

    CN121044622A

  • Silicon-carbon negative electrode material with multi-layer core-shell structure and preparation method and application thereof

    CN121044622B

  • Solid electrolyte doped silicon-carbon composite material, preparation method and application thereof

    CN121076100A

  • Solid-state electrolyte doped silicon-carbon composite material, preparation method and application thereof

    CN121076100B

  • Titanium-doped silicon carbon negative electrode material and preparation method thereof

    CN121617947A